1980
DOI: 10.1001/jama.1980.03310200031021
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin Ointment for Ocular Prophylaxis of Neonatal Chlamydial Infection

Abstract: We compared the efficacy of erythromycin ophthalmic ointment vs 1% silver nitrate drops for the prevention of neonatal conjunctivitis or respiratory tract infection from Chlamydia trachomatis. The organism was isolated from the cervix of 67 (12%) of 572 pregnant women. They gave birth to 559 infants who were randomly assigned to either prophylaxis immediately after birth. Thirty-six of 60 infants born to Chlamydia-positive women received silver nitrate; 24 received erythromycin. Twelve (33%) of the 36 infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 8 publications
2
26
0
Order By: Relevance
“…Ocular prophylaxis with local erythromycin has been attempted in some units in the United States but it is not completely effective in preventing conjunctivitis and in no way alters the incidence of C trachomatis infection in the respiratory tract. 18 Respiratory infections in the first four months are frequently caused by C trachomatis.3 The rate in this study is an underestimate as seven children with conjunctivitis were treated with systemic antibiotics and so were no longer susceptible to C trachomatis respiratory infection, so the true rate was six of 36 (17%). As these seven children suffered the most severe conjunctivitis, the rate in untreated infants may even be higher.…”
Section: Discussionmentioning
confidence: 75%
“…Ocular prophylaxis with local erythromycin has been attempted in some units in the United States but it is not completely effective in preventing conjunctivitis and in no way alters the incidence of C trachomatis infection in the respiratory tract. 18 Respiratory infections in the first four months are frequently caused by C trachomatis.3 The rate in this study is an underestimate as seven children with conjunctivitis were treated with systemic antibiotics and so were no longer susceptible to C trachomatis respiratory infection, so the true rate was six of 36 (17%). As these seven children suffered the most severe conjunctivitis, the rate in untreated infants may even be higher.…”
Section: Discussionmentioning
confidence: 75%
“…540,541 A variety of interventions have been evaluated for prevention of ophthalmia neonatorum in developed countries, mostly in hospital settings, and have largely focused on the prevention of gonococcal infections. [542][543][544][545] These studies have suggested that silver-nitrate, tetracycline, or erythromycin ointments given prophylactically are equivalent in efficacy. 546,547 The WHO recommends 1% silver-nitrate solution, 1% tetracycline ointment, or 2.5% povidone-iodine within 1 hour of delivery.…”
Section: Prevention and Treatment Of Ophthalmia Neonatorummentioning
confidence: 99%
“…trachomatis infection, a prevalent sexually transmitted proved a definite role of C. trachomatis infection in adverse disease, is associated with complications like ectopic pregnancy outcome. [1][2][3][4] If not treated on time their newborns pregnancy, fallopian tube block and adverse pregnancy run a 20-40% risk of developing chlamydial conjunctivitis [7][8][9] outcome. [1][2][3][4] In majority of the women the infection with this and a 10-20% risk of developing chlamydial pneumonia.…”
Section: Abstract: Chlamydia Trachomatis Antigen Blocking Antibodymentioning
confidence: 99%